trục căn thức ở mẫu: \(\frac{1}{1+3\sqrt[3]{2}-2\sqrt[3]{4}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b) Đặt P = ...
\(P=\sqrt{\left(\frac{1}{\sqrt{ab+a+2}}+\frac{1}{\sqrt{bc+b+2}}+\frac{1}{\sqrt{ca+c+2}}\right)^2}\)
\(\le\sqrt{3\left(\frac{1}{ab+1+a+1}+\frac{1}{bc+1+b+1}+\frac{1}{ca+1+c+1}\right)}\)
\(\le\sqrt{\frac{3}{4}\left(\frac{1}{ab+1}+\frac{1}{bc+1}+\frac{1}{ca+1}+\frac{1}{a+1}+\frac{1}{b+1}+\frac{1}{c+1}\right)}\)
\(=\sqrt{\frac{3}{4}\left(\frac{a}{a+1}+\frac{1}{a+1}+\frac{b}{b+1}+\frac{1}{b+1}+\frac{c}{c+1}+\frac{1}{c+a}\right)}=\sqrt{\frac{9}{4}}=\frac{3}{2}\)
Dấu "=" xảy ra \(\Leftrightarrow\)\(a=b=c=1\)
\(A=\frac{3}{x^4-x^3+x-1}-\frac{1}{x^4+x^3-x-1}-\frac{4}{x^5-x^4+x^3-x^2+x-1}\)
\(=\frac{3}{\left(x-1\right)\left(x^3+1\right)}-\frac{1}{\left(x+1\right)\left(x^3-1\right)}-\frac{4}{\left(x-1\right)\left(x^4+x^2+1\right)}\)
\(=\frac{3}{\left(x-1\right)\left(x+1\right)\left(x^2-x+1\right)}-\frac{1}{\left(x+1\right)\left(x-1\right)\left(x^2+x+1\right)}-\frac{4}{\left(x-1\right)\left(x^4+x^2+1\right)}\)
\(=\left[\frac{3}{\left(x-1\right)\left(x+1\right)\left(x^2-x+1\right)}-\frac{1}{\left(x+1\right)\left(x-1\right)\left(x^2+x+1\right)}\right]-\frac{4}{\left(x-1\right)\left(x^4+x^2+1\right)}\)
\(=\left[\frac{3\left(x^2+x+1\right)}{\left(x-1\right)\left(x+1\right)\left(x^2-x+1\right)\left(x^2+x+1\right)}-\frac{x^2-x+1}{\left(x+1\right)\left(x-1\right)\left(x^2+x+1\right)\left(x^2-x+1\right)}\right]-\frac{4}{\left(x-1\right)\left(x^4+x^2+1\right)}\)\(=\frac{3x^2+3x+3-x^2+x-1}{\left(x-1\right)\left(x+1\right)\left(x^2-x+1\right)\left(x^2+x+1\right)}-\frac{4}{\left(x-1\right)\left(x^4+x^2+1\right)}\)
\(=\frac{2x^2+4x+2}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}-\frac{4}{\left(x-1\right)\left(x^4+x^2+1\right)}\)
\(=\frac{2x^2+4x+2}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}-\frac{4\left(x+1\right)}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}\)
\(=\frac{2x^2+4x+2-4x-4}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}=\frac{2x^2-2}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}=\frac{2\left(x^2-1\right)}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}\)
\(=\frac{2\left(x-1\right)\left(x+1\right)}{\left(x-1\right)\left(x+1\right)\left(x^4+x^2+1\right)}=\frac{2}{x^4+x^2+1}\)
\(\Rightarrow A=\frac{2}{x^4+x^2+1}\left(x\ne\pm1\right)\)
Ta có: \(x^4+x^2+1=\left(x^2\right)^2+2.x^2.\frac{1}{2}+\frac{1}{4}+\frac{3}{4}=\left(x^2+\frac{1}{2}\right)^2+\frac{3}{4}>0\forall x\)
Vậy A > 0 với mọi \(x\ne\pm1\)
Đặt \(a=2x;\sqrt[3]{2-8x^3}=t\)
=> \(\hept{\begin{cases}\left(2a-1\right)t=a\\t^3+a^3=2\end{cases}}\)
<=>\(\hept{\begin{cases}a+t=2at\\\left(a+t\right)^3-3at\left(a+t\right)=2\end{cases}}\)=> \(\hept{\begin{cases}a+t=2at\\\left(a+t\right)^3-\frac{3}{2}\left(a+t\right)^2-2=0\end{cases}}\)
=> \(\hept{\begin{cases}a+t=2\\at=1\end{cases}}\)
=> \(a=t=1\)
=> \(x=\frac{1}{2}\)
Vậy \(x=\frac{1}{2}\)